2021
DOI: 10.3390/ijerph18105066
|View full text |Cite
|
Sign up to set email alerts
|

Does Trypsin Oral Spray (Viruprotect®/ColdZyme®) Protect against COVID-19 and Common Colds or Induce Mutation? Caveats in Medical Device Regulations in the European Union

Abstract: Background: nasal or oral sprays are often marketed as medical devices (MDs) in the European Union to prevent common cold (CC), with ColdZyme®/Viruprotect® (trypsin/glycerol) mouth spray claiming to prevent colds and the COVID-19 virus from infecting host cells and to shorten/reduce CC symptoms as an example. We analyzed the published (pre)-clinical evidence. Methods: preclinical: comparison of in vitro tests with validated host cell models to determine viral infectivity. Clinical: efficacy, proportion of user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
(159 reference statements)
0
6
0
Order By: Relevance
“…After thorough data analysis, the authors concluded that exogenous trypsin exposure might not only be ineffective, but might even trigger adverse effects on viral transmission, susceptibility/infection and mutation. 23 In contrast, no hRV escape mutants could be detected after 10 passages in the presence of low-level iota-carrageenan. 9 As iota-carrageenan non-specifically envelops the virus, thereby preventing interaction between virus and cellular surface, development of resistance due to the occurrence of escape mutants is unlikely.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…After thorough data analysis, the authors concluded that exogenous trypsin exposure might not only be ineffective, but might even trigger adverse effects on viral transmission, susceptibility/infection and mutation. 23 In contrast, no hRV escape mutants could be detected after 10 passages in the presence of low-level iota-carrageenan. 9 As iota-carrageenan non-specifically envelops the virus, thereby preventing interaction between virus and cellular surface, development of resistance due to the occurrence of escape mutants is unlikely.…”
Section: Discussionmentioning
confidence: 98%
“…A recent review identified 14 such sprays in development; many of these sprays are already marketed as medical devices in Europe. 23 However, a closer look often reveals a lack of safety and efficacy data. Huijghebaert et al investigated a trypsin containing mouth spray (Viroprotect ® , ColdZyme ® ) for which it was claimed to prevent common cold and COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…It can hydrolyse natural or denatured proteins, fibronectin and mucin into smaller peptides or amino acids. 102 This selective hydrolytic effect of trypsin is mainly related to the structure of the protein. It is said that trypsin only hydrolyses denatured protein, which can be produced under the influence of external physical or chemical factors.…”
Section: Therapeutic Use Of Trypsinmentioning
confidence: 99%
“…We have read the comment from Davison with great interest [1]. We are grateful that he highlighted and reported these errors on our end, and regret to inform the readership that the paper on trypsin oral spray indeed contains errors [2]. These errors relate to the misinterpretation of one study that reported on the use of ColdZyme mouth spray in endurance athletes and its impact on the duration of upper respiratory tract infection (URTI) symptoms [3].…”
mentioning
confidence: 99%
“…Related to this error (we obtained the numbers the wrong-way-round), Table 2 should also be adapted. We copied the initial Table 2 from the Huighebaert et al paper [2] and have adapted the table section on the Davison study [3]. The former and adapted versions of Table 2 are provided, and the adaptations are discussed below.…”
mentioning
confidence: 99%